Pengembangan Kreativitas dan Kompetensi Analisis Data Kuantitatif untuk Guru-Guru di Kepulauan Seribu - Hidajat, Flavia Aurelia; Rahayu, Wardani; Meiliasari, Meiliasari (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
This socialization aims to develop the creativity and competence of quantitative data analysis for teachers in the Thousand Islands. The method of this socialization is delivering material interactively and practically using a laptop. The participants of this socialization were 25 teachers in the Seribu Islands. This socialization was carried out for two days at the Seribu Islands school. This socialization forms teachers into groups to carry out analysis and discuss together. The results of this socialization activity are the conclusions from the results of the questionnaire after the socialization, namely (1) 100% of participants stated that they easily understood the material; (2) 92% of participants stated that the duration of the socialization was following the material presented; (3) 100% of participants stated that the presenters had detailed and clear presentation of the material; (4) 100% of participants acquire new knowledge. The socialization went smoothly because the participants were enthusiastic about practicing quantitative data analysis using SPSS. The obstacle to this socialization is the limitation of the duration of socialization activities.